Distinguishing two distinct types of salivary extracellular vesicles: a potential tool for understanding their pathophysiological roles - Ogawa, Yuko; Miura, Yuri; Ikemoto, Mamoru; Ohnishi, Atsushi; Goto, Yoshikuni; Aoki, Kazuma; Motokurumada, Yuki; Akimoto, Yoshihiro; Endo, Tamao; Tsujimoto, Masafumi; Yanoshita, Ryohei (Frontiers in Molecular Biosciences, 2024)
Extracellular vesicles (EVs), which are found in almost all cells and human body fluids, are currently being studied as a source of pathophysiological information. Previously, we demonstrated that at least two types of EVs can be isolated from human whole saliva (WS) using enzymatic activity of dipeptidyl peptidase IV (DPP IV) as a marker for differentiating the EV subsets. In the present study, EV fractions, termed EV-I 20 k-ppt and EV-II 100 k-ppt, were prepared by a combination of size-exclusion chromatography of improved condition and sequential centrifugation. The EV-I 20 k-ppt fraction contained medium/large EVs with a diameter of 100–1,000 nm, including aminopeptidase N (APN), mucin 1, ezrin, and Annexin A1. EV-II 100 k-ppt contained small EVs with a diameter of 20–70 nm, with DPP IV and CD9, programmed cell death 6-interacting protein, and tumor susceptibility gene 101 as characteristic proteins. Proteomic analyses also revealed distinctive repertoires of constituent proteins. Immunoprecipitation of several membrane proteins of the EVs with respective antibodies suggested their differential local membrane environment between the two types of salivary vesicles. Thus, we identified two distinctive types of EVs, one is APN/MUC1- rich EVs (EV-I, large/medium EVs) and the other is DPP IV/CD9-rich EVs (EV-II, small EVs). Furthermore, analysis of the binding of the EVs to coronavirus spike proteins showed that EV-II 100 k-ppt, but not EV-I 20 k-ppt, significantly bound to the spike protein of Middle East respiratory syndrome coronavirus (MERS-CoV). Finally, we developed a simple method to prepare two distinctive EVs from only 1 mL of human WS using sequential immunoprecipitation. Elucidating the features and functions of these two types of salivary EVs may help us understand their pathophysiological roles in the oral cavity and gastrointestinal tract.